موقف قريش من الزعامة السياسية في يثرب قبيل الهجرة - العتيبي، عبدالله بن عويض (جامعة الإمام محمد بن سعود الاسلامية - عمادة البحث العلمي, 2021)
تناول هذا البحث دراسة حديثة، تتمثل في إبراز دور قريش ومكانة مكة الدينية والاقتصادية عند العرب قبل الإسلام، حيث أسهمت هذه المكانة التي حظيت بها قريش في محاولة إيجاد زعامة سياسية موالية في يثرب بهدف رفض دعوة النبي صلى الله عليه وسلم وتعطيل الهجرة وتكوين الدولة الإسلامية. ونتيجة لالتقاء المصالح مع اليهود تم العمل على محاولة تغيير نظام يثرب السياسي الذي لم يكن ملكيا ولم يعرف حكومة الملأ التي عرفتها مكة والطائف، حيث كانت مقسمة إلى العديد من الآطام التي توضح الحالة السياسية ليثرب قبل الإسلام نتيجة الحروب التي وقعت بين الأوس والخزرج. وقد اتخذت قريش من الطائف أنموذجا في رفض الدعوة الإسلامية، حيث كانت زعامة الطائف موالية لقريش، لذلك سعت لتنصيب زعامة سياسية موالية لقريش في يثرب، يتم دعمها داخليا من اليهود وخارجيا من قريش، لتقوم بهذه المهمة، فكان الخيار يتمثل في شخصية عبد الله بن أبي بن سلول الذي انطبقت عليه الشروط ليكون رجل تلك المرحلة.
This research dealt with the role and the religious and economic status that the "Quraysh" enjoyed in Makkah among the Arabs before Islam, where this position that the "Quraish" had enjoyed in trying to find a political leadership loyal to it in "Yathrib" with the aim of rejecting the prophet’s exaggerated "Daawa", disrupting immigration (i.e. Alhijra), and establishing the young Islamic state. As a result of the convergence of interests with the Jews, the "Quraysh" worked on trying to change the political system of "Yathrib", which was not a monarchy and did not know the "Malaa" government that Makkah and "Taif" knew, and the city was divided into several eforts showing its political status before Islam as a result of the wars that took place between the "Aws" and "Khazraj" tribes. The Quraysh took from Taif a model in rejecting the Islamic "Daawa" and tried to apply it in "Yathrib", as the political leadership in "Taif" was loyal to "Quraish", She sought the same in "Yathrib" relying on the support of its Jews, and the choice was on the personality of "Abdullah Ibn Obai Ibn Saloul", who met the conditions to be a man of that important stage.
Keywords: التاريخ الإسلامي -- الزعامة السياسية -- الحضارة الإسلامية -- الهجرة الإسلامية -- يثرب